IMPROVEMENT OF THE TECHNOLOGICAL PROCESS OF ROUTE MOVEMENT - Firsov, A. D.; Zvieriev, P. V.; Shapovalov, A. V.; Michailov, M. V. (Systems and Technologies, 2019)
The problem of reducing fuel consumption by buses, taxis and trucks is urgent. Fuel economy and efficient use of the power resources of the motor vehicle can significantly reduce fuel costs and maintenance. In today's passenger transportation, fuel and lubricant costs, the savings on these consumables make it possible to significantly reduce transportation costs for transport companies and trucking companies.The purpose of the study is to analyze the situation on the road, helping drivers to slow down and accelerate with calculated efficiency. For the stationary route, you can use a terrain map and relief, allowing the driver to release gas in advance when approaching the turns, forks and stops where you have to brake. Analyzing the route parameters and engine modes allows you to provide guidance on the choice of speed mode and transmission. As a result, there is no need for frequent accelerations and brakes, which has a positive effect on fuel consumption.The route under consideration identifies the relief features of the route, which, above all, enables the development of a more efficient driving schedule of the vehicle, which in turn will allow the driver to use the engine power with maximum benefit based on these data. External velocity characteristics, traction-velocity balance and fuel and economic characteristics of the engine of the vehicle under consideration are calculated. Based on this data, the driving mode for each section of the route is selected to match the lowest fuel consumption and engine power. The problem with the implementation of  this plan is to communicate to the driver information on the optimal use of engine power, depending on road conditions. On the one hand, an application can be developed for the driver that will offer driving modes, but control of the parameters and the reaction of the driver in real operating conditions may not be effective. Therefore, the approach implemented in the work is rather a tool for automating the movement process. Obviously, after the full automatic movement of the vehicle is realized, the next steps will be the optimization of transportation costs.